Hangman salen platforms containing two xanthene scaffolds - Bachmann, Julien; et al. (Journal of Organic Chemistry, 2006)
A synthetic strategy for the construction of chiral salen ligands bearing two rigid xanthene spacers functionalized with carboxylic acid and ester groups is presented. Suzuki cross-coupling methodology is used to furnish the appropriately functionalized xanthene spacers to a salicyladehyde, which is subsequently condensed with (1R, 2R)-(-)-1,2-diaminocyclohexane to produce salen ligands featuring an expandable molecular cleft capable of multiple hydrogen-bonding interactions in addition to metallosalen oxidation chemistry. The ability of these "Hangman" platforms to support multielectron chemistry mediated by proton-coupled electron transfer (PCET) is established by their proclivity to promote the catalytic disproportionation of hydrogen peroxide to oxygen and water via a high-valent metal oxo. Within this functionalized Hangman framework, the stereochemistry of the cyclohexyl backbone of the salen platform is revealed in the epoxidation of 1,2-dihydronaphthalene by the metal oxo.